IMPLEMENTASI MANAJERIAL DALAM MENINGKATKAN KINERJA KEPALA MADRASAH DI MTs SWASTA DARUL HIKMAH TELUK MEKU PKL. BERANDAN - Fachrul Rozi, Novita Sari, Muhammad Habib (Pusdikra Publishing, 2020)
The aims of this study are as follows: 1) To find out how managerial is at Private Mts Darul Hikmah Teluk Meku Pkl Berandan; 2) To find out how the performance of Madrasah Principals at Mts Swasta Darul Hikmah Teluk Meku Pkl Berandan; 3) To find out whether managerial implementation can improve the performance of Madrasah Principals at Private MTs Darul Hikmah Teluk Meku Pkl Berandan. The performance of the Madrasah Principal can be said to be an illustration of the good and bad results achieved by education managers in the process of implementing the education process in schools. This type of research is qualitative research. There are two kinds of data sources in this study, namely primary data sources and secondary data sources. Primary data sources include the subject, namely the principal and teacher of MTs Darul Hikmah Teluk Meku Pkl. Laman, while the secondary data sources are in the form of documents, written notes related to the research focus. Data collection techniques by means of observation, interviews and documentation. The data obtained during the study were analyzed by data reduction steps, data presentation, and drawing conclusions. Meanwhile, the data validity test was carried out with persistence and triangulation observations. The triangulation used in this research is source triangulation. The results of this study indicate that regarding the managerial skills of the madrasah principal in improving the quality of learning, there are several indicators, namely, technical skills, conceptual skills, human relations skills, learning planning, implementation of the learning process and assessment of learning outcomes. In the technical mastery of madrasah principals to improve the quality of learning, madrasah principals are armed with their experiences while being principals and madrasah principals utilize school facilities and infrastructure such as using LCDs when learning For human relations skills, the principal always communicates with the teachers by greeting them every day. And for conceptual skills, to solve problems faced by the head of the madrasah, he always invites teachers to meet so that problems can be resolved.